2023
DOI: 10.1038/s41598-023-36198-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of silver nanoparticles on tropane alkaloid production of transgenic hairy root cultures of Hyoscyamus muticus L. and their antimicrobial activity

Abstract: The utilization of nanotechnology and biotechnology for enhancing the synthesis of plant bioactive chemicals is becoming increasingly common. The hairy root culture technique can be used to increase secondary metabolites such as tropane alkaloids. Agrobacterium was used to induce hairy roots from various explants of Hyoscyamus muticus. The effect of nano-silver particles (AgNPs) at concentrations of 0, 25, 50, 100, and 200 mg/L on tropane alkaloids synthesis, particularly hyoscyamine and scopolamine, was studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(1 citation statement)
references
References 46 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…A serine/threonine-protein kinase CTR1-like isoform X1, as the target of stu-miR477b-5p, was demonstrated to be involved in plant root auxin homeostasis [59]. Tropinone reductase-like 3 was identified as the candidate target gene of stu-MIR5303j-p5; it was demonstrated to play a key role in the aberrant cell-file rotation of the root differentiation zone [60]. An uncharacterized protein LOC102590046 isoform X1 was identified as the candidate target gene of PC-3p-230042_5; GO function analysis showed that this protein is involved in root development and cell wall repair.…”
Section: Discussionmentioning
confidence: 99%
“…A serine/threonine-protein kinase CTR1-like isoform X1, as the target of stu-miR477b-5p, was demonstrated to be involved in plant root auxin homeostasis [59]. Tropinone reductase-like 3 was identified as the candidate target gene of stu-MIR5303j-p5; it was demonstrated to play a key role in the aberrant cell-file rotation of the root differentiation zone [60]. An uncharacterized protein LOC102590046 isoform X1 was identified as the candidate target gene of PC-3p-230042_5; GO function analysis showed that this protein is involved in root development and cell wall repair.…”
Section: Discussionmentioning
confidence: 99%